2016
DOI: 10.1093/bib/bbw042
|View full text |Cite
|
Sign up to set email alerts
|

Computational methods for identifying miRNA sponge interactions

Abstract: Recent findings show that coding genes are not the only targets that miRNAs interact with. In fact, there is a pool of different RNAs competing with each other to attract miRNAs for interactions, thus acting as competing endogenous RNAs (ceRNAs). The ceRNAs indirectly regulate each other via the titration mechanism, i.e. the increasing concentration of a ceRNA will decrease the number of miRNAs that are available for interacting with other targets. The cross-talks between ceRNAs, i.e. their interactions mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 73 publications
0
83
0
Order By: Relevance
“…For the ground truth of validation, we combine the experimentally validated miRNA sponge interactions from [8] with miRSponge [57]. In total, we have obtained 99 experimentally validated miRNA sponge interactions (details in Additional file 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the ground truth of validation, we combine the experimentally validated miRNA sponge interactions from [8] with miRSponge [57]. In total, we have obtained 99 experimentally validated miRNA sponge interactions (details in Additional file 6).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the hypothesis, a pool of RNAs acting as ceRNAs (also called miRNA sponges), such as lncRNAs, pseudogenes, mRNAs and circular RNAs (circRNAs), compete with each other by sponging miRNAs for interactions. Previous studies have shown that miRNA sponges play important roles in the physiology and development of human cancers [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2015) showed that miR-146b-5p functioned as a tumor suppressor by targeting TRAF6 and predicted the prognosis of human gliomas. Recent studies showed that lncRNA could function as a miRNA sponge to regulate mRNA expression levels (Le, Zhang, Liu, & Li, 2017). CeRNA was proved to be an effective posttranscriptional regulation mechanism of lncRNAs on downstream target transcripts (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown that functionally similar miRNAs always appear in similar diseases; therefore many computational models were proposed to identify novel miRNA-disease associations [13,[41][42][43][44][45][46]. For example, Jiang et al [31] analyzed and improved disease-gene prediction model, introduced the principle of hypergeometric distribution and how to use it, and discussed its application in prediction model and its actual effect.…”
Section: Introductionmentioning
confidence: 99%